Grounded Theory: Study of Aboriginal Nations - Gary L. Evans (Grounded Theory Review: An International Journal)
Recently, Elers (2016) published an article stating the importance of using Classical Grounded Theory (CGT) when researching indigenous populations. This article puts forward CGT as a viable and necessary tool for researching this complex subject as it requires researchers to utilize multiple data sources and, as in this particular project, can be used by multiple disciplinary teams. Canada has much to do to rebuild the trust of the indigenous people of Canada. CGT shows promise as a methodology that gets to the root of the issues and offers one of the best opportunities to develop a theory that can be part of the constructive healing process going forward.